Inovasi Digital dalam Penguatan Identitas Budaya Lokal: Digitalisasi Tradisi Pawonan di Kampung Budaya Polowijen, Kota Malang - erawanto, very; Fajar, Yusri; Khoirel Abidah, Nudya Kuntum; Hikmawati, Rosyidatul (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Abstract This research explores digital innovation in strengthening local cultural identity through the digitization of the Pawonan tradition at the Polowijen Cultural Village (KBP) in Malang City. The study focuses on implementing a digital catalog as a strategy to document, promote, and preserve Pawonan as an intangible cultural heritage. The aim is to create a structured, accessible, and participatory digital documentation system to enhance the tradition’s visibility, tourism appeal, and sustainability. Using a participatory-collaborative method based on Asset-Based Community Development (ABCD), the research actively involved the community as subjects in cultural mapping, audiovisual documentation, and digital catalog design. The results demonstrate that the developed digital catalog successfully integrates multimedia data (text, photos, videos) with philosophical narratives of the Pawonan tradition in a bilingual format (Indonesian-English), improving public accessibility and awareness of the cultural heritage. This research contributes by providing an adaptive cultural digitization model for local communities, supporting technology-based preservation, and reinforcing cultural identity in a modern context. Keywords: Cultural Digitization; Digital Catalog; Pawonan Tradition; Polowijen Cultural Village; Cultural Preservation